Improvement of MASLD and MASH by suppression of hepatic N-acetyltransferase 10 - Yanying Yang; Jie Lu; Yuejun Liu; Ni Zhang; Yunchen Luo; Mingyue Ma; Zhixia Dong; Shuo Zhang; Ming-Hua Zheng; Cheng-Chao Ruan; Xinjian Wan; Cheng Hu; et al. (Elsevier, 2024)
Objective: Metabolic dysfunction-associated steatotic liver disease (MASLD) and metabolic dysfunction-associated steatohepatitis (MASH) are characterized by excessive triglyceride accumulation in the liver. However, due to an incomplete understanding of its pathogenesis, more efforts are needed to identify specific and effective treatments. N4-acetylcytidine (ac4C) is a newly discovered RNA modification to regulate mRNA. N-acetyltransferase 10 (NAT10) has not been fully explored in MASLD and MASH. Methods: The clinical relevance of NAT10 was evaluated based on its expression in various mouse and human models of MASLD and MASH. Acetylated RNA immunoprecipitation sequencing and mRNA stability assays were used to explore the role of NAT10 in regulating ac4C modification and expression of target genes. Genetically engineered mice were employed to investigate the role of NAT10 in MASLD and MASH progression. Results: Hepatic NAT10 expression was significantly increased in multiple mice and humans of MASLD and MASH. Genetic knockout of NAT10 protected mice from diet-induced hepatic steatosis and steatohepatitis, whereas overexpression of NAT10 exacerbated high-fat-diet-induced liver steatosis. Mechanistically, NAT10 binds to Srebp-1c mRNA, promoting its stability and expression, thereby upregulating lipogenic enzymes. Treatment with Remodelin, a NAT10-specific inhibitor, effectively ameliorates liver steatosis and dyslipidemia in a preclinical mouse model. Conclusions: Our findings indicate that NAT10 could regulate lipid metabolism in MASLD and MASH by stabilizing Srebp-1c mRNA and upregulating lipogenic enzymes. This study highlights the role of NAT10 and RNA acetylation in the pathogenesis of MASLD and MASH. Thus, our findings suggest a promising new therapeutic approach, such as the use of NAT10 inhibitor, for treating metabolic liver disease.